On being African and Reformed? Towards an African Reformed theology enthused by an interlocution of those on the margins of society - Tshaka, Rothney S. (HTS teologiese studies, 2014)
This article was first given as an inaugural lecture. As such, it sets out a particular agenda for the researcher’s interest. Here, the notions of being African and Reformed are interrogated. The research notes that these notions are rarely used in the same vein. It is admitted that notions tend to pick up different meanings as they evolve, so these notions are especially seen in that light. The theological hegemony, which in the South African academic circles had become enveloped in the Reformed identity, is here forced to critically consider Africanness. This is considered significant, especially in a context where the Christian faith is seen to be flourishing in the global South. The article challenges attempts at explaining what Africanness mean as a front to perpetuate a status quo that from its inception never thought much of Africa and or Africanness. The author argues that the African Reformed Christian must acknowledge is status as a partial outsider in Reformed theological discourses.